Poder de polícia e poder punitivo : o direito administrativo no sistema penal brasileiro - Rigon, Bruno Silveira (2021)
This thesis has as its object of study the police power in the Brazilian penal system. The research intends to analyze the relationship between police power and state punitive power, that is, it seeks to understand the legal-political rationality of administrative law present in the Brazilian criminal justice system, with a limited focus on the practices and discourses of legal actors in the drug war context. Two central questions led to this investigation. First: what are the knowledge-power relations between the police power – and the categories arising from the administrative law that resolve around it – with the punitive state power in Brazil? Second: how do such relationships occur specifically in the Brazilian context of the war on drugs? The general objective of this research, therefore, is to make visible the invisible administrative rationality within the Brazilian penal system. Our central hypothesis argued that the manifestation of state authoritarianism remains more evident and latent when police power and punitive power intertwine, as effects are created that produce legal truths from invisible administrative law mechanisms in the plots of relations of the punitive power. Throughout the investigation, we found that the relationship of police power in the Brazilian criminal justice system has its architectural foundations in the categories of administrative discretion, which underlies police discretion; presumption of legitimacy and veracity of the acts of the public power, which legitimizes police testimony in drug trafficking crimes; and the principle of supremacy of the public interest over the private, which justifies violence and state arbitrariness in the name of a superior collective interest in fighting crime. These are dispositive from administrative law that convey a certain authoritarian legal-political rationality of the administrative area, influenced by the legal discourse of the doctrine of national security, to the functioning of the institutions of the Brazilian penal system. The methodology adopted in this work was based on the proposal of historical investigation from the Foucaultian genealogy. Bibliographic review and document analysis were used, based on the examination of legislation, legal discourses in lectures, interviews, articles, books and conferences, manual of the Superior War School and Brazilian police institutions, among other sources of historiographical research.